Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1128/cdli.10.6.1141-1146.2003
|View full text |Cite
|
Sign up to set email alerts
|

ImmunochromatographicBrucella-Specific Immunoglobulin M and G Lateral Flow Assays for Rapid Serodiagnosis of Human Brucellosis

Abstract: To fulfill the need for a simple and rapid diagnostic test for human brucellosis, we used the immunochromatographic lateral flow assay format to develop two assays, one for the detection of Brucella-specific immunoglobulin M (IgM) antibodies and one for the detection of Brucella-specific IgG antibodies. The diagnostic values of these tests were examined. The tests are shown to detect acute, persistent, and relapsing disease and can be used to monitor treatment. The sensitivity of Brucella IgM and IgG flow assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 24 publications
(16 reference statements)
5
104
0
1
Order By: Relevance
“…This could be an important aspect in countries such as Egypt where the disease is widely spread. Furthermore, our results are in agreement with the high sensitivity and specificity observed for the flow assay by earlier reports from Spain [19], Turkey [21,22], and Kazakhstan [21]. Therefore, in the absence of the laboratory support, the flow assay may be used for the confirmation of brucellosis in febrile patients with clinical suspicion of brucellosis by testing a drop of blood collected by finger prick.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This could be an important aspect in countries such as Egypt where the disease is widely spread. Furthermore, our results are in agreement with the high sensitivity and specificity observed for the flow assay by earlier reports from Spain [19], Turkey [21,22], and Kazakhstan [21]. Therefore, in the absence of the laboratory support, the flow assay may be used for the confirmation of brucellosis in febrile patients with clinical suspicion of brucellosis by testing a drop of blood collected by finger prick.…”
Section: Discussionsupporting
confidence: 79%
“…For the lateral flow assay, 5 µl of serum followed by 130 µl of running fluid were added to the sample application pad in the sample well of the plastic assay device (Royal Tropical Institute, Amsterdam, The Netherlands) [19]. The assay was read after 10 to 15 minutes by visual inspection for staining of the test and control lines in the assay window of the device.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Clinical features of the 13 patients of brucellosis were typical of the disease (Table 4). Three newly (5), sweats (9), myalgia (11), and arthralgia (18). ‡Any of the screening tests positive.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies have shown that even in endemic regions the LFA IgM/IgM test has a sensitivity and specificity of~ 96%, even when used in endemic areas. 18,33,34 The performance of screening agglutination tests (either the RB or slide agglutination test) occasionally is inferior to the tube agglutination test, which has different incubation times and conditions. 35 Confirmatory serologies performed in this study included the tube agglutination test (with a 1 of 160 titer cutoff) and the 2-ME test (that differentiates IgM from IgG antibodies, indicating acute infection) to enhance the specificity of testing; previous studies from Peru and elsewhere have shown these criteria to be strongly suggestive of a new episode of brucellosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation